Improved dredge material management for the Great Barrier Reef Region: Synthesis report - (:unkn) unknown (Great Barrier Reef Marine Park Authority, 2013)
The Department of Sustainability, Environment, Water, Population and Communities and the Great Barrier Reef Marine Park Authority commissioned Sinclair Knight Merz Pty Ltd and Asia-Pacific Applied Science Associates to undertake a study on Improved Dredge Material Management for the Great Barrier Reef Region. The study provides analysis and information to inform future dredge material management for the five major ports (Ports of Cairns, Townsville, Gladstone, Abbot Point, Hay Point) and one marina (Rosslyn Bay) in the Great Barrier Reef World Heritage Area. The study examines differences in sediment migration patterns from placing dredge material at hypothetical alternative and currently used placement sites. It is the first study to both incorporate the effects of regional oceanic currents in modelling dredge material migration and model dredge material migration over a period of 12 months, providing insight into the behaviour and potential risks of dredge material over time. The information generated by this study is high level and is not intended to replace the detail required as part of an environmental impact assessment process for any future dredge material placement operations.
Keywords: Dredging; Coastal development; Water quality; Reef-wide